PENGARUH PELAYANAN TERHADAP KEPUASAN NASABAH PADA KANTOR PT BANK BCA CABANG LUBUKLINGGAU - Ronal Aprianto (Jurnal Ilmiah Ekonomi Global Masa Kini)
The goal of this research was to know the effect of service on customers satisfaction in BCA Bank Lubuklinggau. The Population of this research was an of the customers which used Electronic Data Capture (EDC) in BCA Bank Lubuklinggau it was 65 persen in 2014, which each month the customer less that 5-6 persen. In this research all of the population used as sample (saturated sample) 65 persen  used  Electronis Data Capture (EDC) Transaction on BCA Bank Lubuklinggau branch. The accidental sampling is used in taking the sample in this research. It was a technioue taking the data in accidental way to make this research easy. In this reseach the technique of data analysis ware vallidity and reability. The asumtion test, reabilitas test and normalitas test regretion clasis aquatio liniear coefisien corelation test and partial test. The result of regretion aquation Y=12,062 + 0,759X . The result of coefisien corelation calculation know the B value was 0,718. It meant that the corelation between service and customer satisfaction in BCA Bank Lubuklinggau was strong. While R2  or determination coefisien was 0,516 or 51,6 % it meant the magmitudt effect of service to the customer satisfaction was 51,6%. While the rest west 48,4 % be effecfeel by the other variables, whish was not include in the  research sush as product, servise, rate of  bank, etc. From the calculation can get the result 8,198 more bigger ttabel  = 1,960. Result t test show Ho rejected and Ha  accepted, its mean variable servicesignificant effect to  satisfaction on pt bank bca branch office lubuklinggau. Key words :Servise and customers satisfaction